高速齿轮传动CAD系统中胶合承载能力模块的实现 - 刘保国; 孙磊; 徐明欣; 刘珂 (Jixie chuandong)
According to GB/Z6431-2003—Calculation of scuffing load capacity of cylindrical,bevel and hypoid gears,the thesis presents an applied program of calculation of scuffing load capacity in the process high speed gear design,and the program was appended to the high speed gear-driven CAD system. By this means,users can obtain the accurate result of calculation of scuffing load capacity rapidly only have to input and select a number of given parameter,the reliability of the high speed gear design CAD system is improved after appended the program to the high speed gear-driven CAD system. The author discussed the establish of database、representation of algorithm and realization of the program,and also the efficiency of the proposed method by project example.